2022
DOI: 10.1111/gcb.16389
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of climate change on deep‐water coral distribution around New Zealand—Will there be suitable refuges for protection at the end of the 21st century?

Abstract: Deep-water corals are protected in the seas around New Zealand by legislation that prohibits intentional damage and removal, and by marine protected areas where bottom trawling is prohibited. However, these measures do not protect them from the impacts of a changing climate and ocean acidification. To enable adequate future protection from these threats we require knowledge of the present distribution of corals and the environmental conditions that determine their preferred habitat, as well as the likely futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 104 publications
1
6
0
Order By: Relevance
“…the combination of outputs from more than one model type) were generated from boosted regression tree (BRT) and random forest (RF) models. These approaches were chosen following previous studies that showed they perform well for similar modelling tasks in the same region (Anderson et al, 2022; Finucci et al, 2021; Stephenson et al, 2023). The modelling approach used here closely follows the method described in Stephenson et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…the combination of outputs from more than one model type) were generated from boosted regression tree (BRT) and random forest (RF) models. These approaches were chosen following previous studies that showed they perform well for similar modelling tasks in the same region (Anderson et al, 2022; Finucci et al, 2021; Stephenson et al, 2023). The modelling approach used here closely follows the method described in Stephenson et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…Following development of JSDMs for benthic taxa for the entire New Zealand EEZ, and on the completion of the further sampling and analyses suggested above, it may be possible to quantitatively incorporate robust predictions of VMEs into future spatial planning efforts in the region. Ideally, this planning would also include other anthropogenic threats to the biodiversity supported by VMEs, including climate change effects (e.g., as in Anderson et al, 2022). Achieving these steps would provide a wealth of additional information on sea oor communities and habitats for use in future spatial planning efforts.…”
Section: Fishing Impacts and Identi Cation Of Vmesmentioning
confidence: 99%
“…The selection of background data for modeling in this study used commonly employed prevalence ratios of 1:1, 1:5, and 1:10, as well as a fixed number of 10,000 points (Phillips et al, 2006;Barbet-Massin et al, 2012;Hysen et al, 2022). Two methods were used to select background points: the target-group background sampling method and kernel density sampling method (Elith et al, 2010;Fitzpatrick et al, 2013;Cerasoli et al, 2017;Georgian et al, 2019;Burgos et al, 2020;Finucci et al, 2021;Georgian et al, 2021;Robinson et al, 2021;Stephenson et al, 2021;Anderson et al, 2022). To select target-group backgrounds for each species, random points were selected from the remaining cold-water coral presences with the selected points within 5 km of occurrences excluded.…”
Section: Background Pointsmentioning
confidence: 99%
“…The target-group sampling method utilizes all occurrences within a target group as biased background data, thereby selecting the background points with the same bias as the sampling effort to reduce the impact of sampling bias in presence-background modeling (Phillips et al, 2009;Merow et al, 2013). Target-group sampling has been found to improve the average performances of tested modeling techniques compared to using randomly selected background data (Phillips et al, 2009;Iturbide et al, 2015), which has been widely used in species distribution predictions in recent years (Cerasoli et al, 2017;Stephenson et al, 2020;Robinson et al, 2021;Stephenson et al, 2021;Anderson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%